Transarterial Chemoembolization for Hepatocellular Carcinoma: An Evaluation of Long-Term Outcomes in Beijing, China - Xi Liang-Wu (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Transarterial chemoembolization (TACE) is a widely used treatment for unresectable hepatocellular carcinoma (HCC). This study aimed to evaluate the long-term outcomes of TACE in a cohort of patients with HCC in Beijing, China. Methods: This retrospective cohort study included patients who underwent TACE for HCC at a tertiary care hospital in Beijing, China, between 2010 and 2018. Data on patient demographics, tumor characteristics, treatment details, and outcomes were collected from medical records. Overall survival (OS) and progression-free survival (PFS) were the primary endpoints. Survival analysis was performed using the Kaplan-Meier method and Cox proportional hazards regression. Results: A total of 352 patients were included in the study. The median follow-up duration was 48 months (range: 6-120 months). The median OS was 36 months, and the 5-year OS rate was 28%. The median PFS was 12 months, and the 3-year PFS rate was 15%. Tumor size, Barcelona Clinic Liver Cancer (BCLC) stage, and alpha-fetoprotein (AFP) level were independent predictors of OS and PFS. Conclusion: TACE can provide long-term survival benefits for patients with HCC in Beijing, China. Tumor size, BCLC stage, and AFP level are important prognostic factors for TACE outcomes.